ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAHKOTA BOGOR TAHUN ANGGARAN 2010 -2014 - Mutiha, Arthaingan H (Jurnal Vokasi Indonesia, 2016)
This study aimed to analyze the financial performance of the City Government of Bogor for the period of 2010 - 2014. The financial performance analysis is performed using ratio analysis such as the degree of decentralization, the ratio of financial independence, ratio of revenue effectiveness, the ratio of direct expenditure compared to total expenditure, the ratio of indirect expenditure compared to total expenditures, and growth ratios. The research concluded that the the ratio of financial independence of City Government of Bogor has a consultatif relation, on the other hand, City Government of Bogor is highly effective in fulfilling its target of achieving its PAD, and also has positive growth over 5 years. But, City Government of Bogor still put its priority in indirect expenditure to total expenditure compared to its direct expense.